THE ROLE OF VITAMIN B12 IN THE DIET – IMPACT ON THE BODY. A LITERATURE REVIEW - Aleksandra Simlat,; Angelika Szwaj,; Aleksandra Cieciora,; Adrianna Świerzyńska,; Natalia Jankowska,; Mateusz Cieciora,; Małgorzata Kawiorska,; Julia Surowiec,; Ilona Mariańska-Wiśniewska,; Tomasz Puszkiel, (International Journal of Innovative Technologies in Social Science, 2026)
Vitamin B12 is a key chemical compound for human health, involved in processes such as homocysteine methylation, DNA synthesis, and mitochondrial function. We present current knowledge on the causes and clinical significance of hypervitaminosis B12 and discuss cobalamin deficiency and excess in selected risk groups: pregnant women, vegetarians and vegans, athletes, and the elderly.Aim of the study: The aim of the study is to assess the impact of vitamin B12 on the functioning of the human body. The analysis focuses on the role of vitamin B12 in the proper functioning of the nervous, hematopoietic, and cardiovascular systems. Furthermore, the study determines the effects of vitamin B12 deficiency and excess in the diet.Material and methods: A literature review was conducted from the PubMed and Google Scholar databases. Key phrases as “vitamin B12”, “cobalamin”, “vitamin B12 deficiency” and “excess vitamin B12” were used.Results and conclusions: Vitamin B12 plays a crucial role in the proper functioning of the human body, influencing the nervous, hematopoietic, and cardiovascular systems. Symptoms such as fatigue, anemia, and impaired concentration have been observed among individuals with vitamin B12 deficiency. The analysis revealed a significant correlation between vitamin B12 supplementation and bodily function. Therefore, it can be concluded that adequate levels of vitamin B12 in the diet are crucial for maintaining health.